Pengaruh Wanita Karir Terhadap Keharmonisan Rumah Tangga dalam Tinjauan Istishlah - Arifin, Zaenal; Nafisah , Chauzatun; Khusna Sabila , Thiyara (El-Qenon: Journal of Islamic Law, 2024)
The Influence of Career Women on Household Harmony from the Perspective of Istishlah. The objectives of this study are: (1) to understand the impact on the household life of female workers in Gedongsari Village, Jumo District, Temanggung Regency, and (2) to analyze Istishlah’s perspective on the influence of female workers on household harmony in Gedongsari Village, Ngadirejo District, Temanggung Regency. The researchers used a quantitative descriptive approach, and data collection techniques included observation, interviews, and documentation. The subjects of this study were the residents of Gedongsari Village who worked as female workers abroad. From the entire research process, the authors obtained the following results: First, the most common occupation among the residents of Gedongsari Village, particularly women, is working abroad as female workers, while their husbands stay at home managing the household. The impact of long-distance relationships due to the absence of the wife’s role at home results in a lack of household harmony. Second, from the perspective of Istishlah, the law permitting women to work as the primary breadwinners can be justified for the sake of family welfare and maintaining the family’s economic sustainability, although this is considered unfavorable by Sharia law, as it contradicts the husband’s primary duty as the main provider.